Tanda Tangan Digital: Otoritas pada Arsip Elektronik - Muhammad Usman Noor (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2021)
The Covid19 pandemic has triggered more massive and extensive use of electronic records due to the Work from Home policy. One of the keys in using electronic records is a digital signature as an authorization stamp for the electronic record. The concept of authentic digital signature and integrity is still unfamiliar to policymakers, which can lead to legality problems in the future. Digital signatures have three levels of validity from basic, advanced, to high. Not all levels produce electronic records that have legal force, so it is necessary to handle with extra concern to their use of digital signature in institutions or organizations. This writing aims to provide an overview of the concept of a digital signature that is authentic, accountable, and integrity. This writing uses a qualitative method. The result of this writing is that the digital signature must go through encryption and verification so that the digital signature has legal force and what its implementation of digital signature in several countries, including Indonesia.